Role of Oxidative Stress in Hepatic and Extrahepatic Dysfunctions During Nonalcoholic Fatty Liver Disease (Nafld) - Gonzalez-Rojas, A; Cabello-Verrugio, C; Tacchi, F; Orozco-Aguilar, J (Hindawi Limited, 2020)
Nonalcoholic fatty liver disease (NAFLD) is a pathology that contains a broad liver dysfunctions spectrum. These alterations span from noninflammatory isolated steatosis until nonalcoholic steatohepatitis (NASH), a more aggressive form of the disease characterized by steatosis, inflammatory status, and varying liver degrees fibrosis. NAFLD is the most prevalent chronic liver disease worldwide. The causes of NAFLD are diverse and include genetic and environmental factors. The presence of NASH is strongly associated with cirrhosis development and hepatocellular carcinoma, two conditions that require liver transplantation. The liver alterations during NAFLD are well described. Interestingly, this pathological condition also affects other critical tissues and organs, such as skeletal muscle and even the cardiovascular, renal, and nervous systems. Oxidative stress (OS) is a harmful state present in several chronic diseases, such as NAFLD. The purpose of this review is to describe hepatic and extrahepatic dysfunctions in NAFLD. We will also review the influence of OS on the physiopathological events that affect the critical function of the liver and peripheral tissues. © 2020 Andrea Gonzalez et al.